Child Health Nurses' experiences of addressing psychosocial risk factors with the families they meet. (24th September 2020) - Engström, Maria; Hiltunen, Johanna; Wallby, Thomas; Lucas, Steven
Abstract: Aim: To examine how child health nurses perceive the routine assessment of psychosocial risk factors in the family environment as well as their self‐reported competence and the present organisational conditions in this context. Method: A mixed‐methods design was used, including three focus group interviews and a web‐based survey. Qualitative data were analysed using systematic text condensation. Quantitative data were analysed at the descriptive level. Results: Nurses expressed that identifying psychosocial risk factors was both important and relevant to their work. They had little formal training and education on most psychosocial risk factors, and they lacked structured methods to address them. In areas where nurses reported more formal education and a structured methodology (depression, parental stress), they rated to a higher degree that they possessed sufficient skills and sense of security. The nurses perceived that they seldom came into contact with families with financial problems, hazardous alcohol use or intimate partner violence. Conclusions: There is a gap between the nurses' attitudes regarding the importance of helping families in need and their ability to do so with the current level of training and methodological support. The results suggest that, in many cases, psychosocial problems remain undetected.